DIABETES MELLITUS AND PERIODONTAL DISEASE –A TWO-WAY ROAD: CURRENT CONCEPTS AND FUTURE CONSIDERATIONS (LITERATURE REVIEW) - Velea, Oana A.; Kralev, Caroline; Onisei, Dan; Onisei, Doina; Nica, Luminita M.; Velea, Iulian P. (European Scientific Journal, ESJ, 2013)
Introduction: Scientists have developed an emerging interest regarding the interrelationship between periodontal disease (PD) and systemic conditions. The best documented condition related to PD is diabetes mellitus (DM). PD is considered to be the sixth complication of DM, both having inflammation process and increased oxidative stress as primary etiologic features. Aim: This paper is aimed at reviewing and evaluating the DM’s role as the main risk factor in PD and the immunological correlations between these two pathologies in search of future and new considerations, beginning with current meanings. ﻿﻿﻿Materials and methods: Epidemiological, immunological, clinical and experimental studies assessing the relationship between PD and DM were selected and studied from medical and dental journals and books. Results: Periodontal inflammation leads to increased circulating cytokines, inflammatory mediators and autoimmune response to infection. The severity of periodontal destruction is demonstrated to be linked to glycemic control effects, other factors also being involved. In diabetic patients with PD, IL-1β, IL-6, and TNF rise gradually with the evolution of DM, consecutive to microangiopatic complications and to the installation of periodontal bone lesions. A significant correlation between metabolic control and the severity and extend of periodontal lesions has also been reported. Conclusions: Although literature is full of articles and studies that demonstrate the close relationship between diabetes and periodontal disease, larger intervention studies are needed to assess if periodontal health improvement can lead to improved metabolic control. It is also considered that the management of oral health should play an important role in diabetes management and vice-versa.